In contrast to Western diet, a plant‐based, high‐fat, low‐sugar diet does not exacerbate retinal endothelial injury in streptozotocin‐induced diabetes. Issue 9 (6th July 2019) - Barakat, Aliaa; Nakao, Shintaro; Zandi, Souska; Sun, Dawei; Schmidt‐Ullrich, Ruth; Hayes, K. C.; Hafezi‐Moghadam, Ali
ABSTRACT: Controversy remains about how diet affects the vascular endothelial dysfunction associated with disordered insulin‐glucose homeostasis. It is postulated that the type and level of certain macronutrients contribute to endothelial dysfunction in vascular diabetes complications. However, it is not well understood how specific macronutrients affect the molecular inflammatory response under conditions of hyperglycemia. Here, we examined retinal microvascular endothelial injury in streptozotocin (STZ)‐diabetic rats fed a laboratory Western diet (WD). WD, characterized by its high content of saturated fat, cholesterol, and sugar, significantly increased retinal leukocyte accumulation and endothelial injury in the STZ‐diabetic rats. Suppression of endothelial NF‐κB signaling in the STZ model reduced the WD‐induced increase in leukocyte accumulation. To isolate the effect of dietary fat, we generated high‐fat diets with varying fatty acid balance and type. These diets contained moderate amounts of carbohydrates but no sugar. We found that neither high levels of saturated or unsaturated fats per se increased retinal leukocyte accumulation and endothelial injury in the STZ‐diabetic rat model but that the combination of high levels of dietary cholesterol with specific saturated fatty acids that are abundant in WD exacerbated leukocyte accumulation and endothelial injury in the retinas of STZ‐diabetic rats.—Barakat, A., Nakao, S., Zandi, S., Sun, D., Schmidt‐Ullrich, R., Hayes, K. C., Hafezi‐Moghadam, A. In contrast to Western diet, a plant‐based, high‐fat, low‐sugar diet does not exacerbate retinal endothelial injury in streptozotocin‐induced diabetes. FASEB J. 33, 10327–10338 (2019). www.fasebj.org